A systematic multitechnique approach for detection and characterization of reversible self‐association during formulation development of therapeutic antibodies. Issue 1 (13th November 2012) - Esfandiary, Reza; Hayes, David B.; Parupudi, Arun; Casas‐finet, Jose; Bai, Shufeng; Samra, Hardeep S.; Shah, Ambarish U.; Sathish, Hasige A.
Abstract In addition to controlling typical instabilities such as physical and chemical degradations, understanding monoclonal antibodies' (mAbs) solution behavior is a key step in designing and developing process and formulation controls during their development. Reversible self‐association (RSA), a unique solution property in which native, reversible oligomeric species are formed as a result of the noncovalent intermolecular interactions has been recognized as a developability risk with the potential to negatively impact manufacturing, storage stability, and delivery of mAbs. Therefore, its identification, characterization, and mitigation are key requirements during formulation development. Considering the large number of available analytical methods, choice of the employed technique is an important contributing factor for successful investigation of RSA. Herein, a multitechnique (dynamic light scattering, multiangle static light scattering, and analytical ultracentrifugation) approach is employed to comprehensively characterize the self‐association of a model immunoglobulin G1 molecule. Studies herein discuss an effective approach for detection and characterization of RSA during biopharmaceutical development based on the capabilities of each technique, their complementarity, and more importantly their suitability for the stage of development in which RSA is investigated. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:62–72, 2013